Assessment on Performance and Emission Characteristics of the CRDI Engine Fueled with Ethanol/Diesel Blends in Addition to EGR. (7th October 2022) - Dineshkumar, C.; Jeyakumar, P. D.; Arvinda Pandian, C. K.; Rajmohan, N.; Elumalai, P. V.; Kamesh, N.; Shaik, Saboor; Sharifpur, Mohsen; Khalilpoor, Nima
Abstract : In this research, the CRDI engine characteristics were analyzed with the aid of exhaust gas recirculation rate (EGR) adoption fueled with ethanol blends. The test fuels were the various blends with ethanol, such as (10% of ethanol + 90% of diesel) E10D90 (20% of ethanol + 80% of diesel), E20D80, and (30% of ethanol + 70% of diesel) E30D70. From the results, it was revealed that performance characteristics were reduced when using a higher concentration of the alcohols mixed with diesel fuel. The blend E30D70 showed that brake thermal efficiency (BTE) without EGR drops by 3.8%, increased by 9.14% of BSFC, a 9.25% decrease in oxides of nitrogen emissions, and slightly decreased CO and HC emissions compared to baseline diesel operation at 60% load condition. The blend E10D90 with 20% EGR shows the highest BTE of 8.87% when compared with base fuel, due to proper fuel mixture taking place in the inlet manifold. The results indicate that the engine runs smoothly, and E30D70 has chosen an optimum blend. A further experiment was performed using E30D70 with different rates of exhaust gas recirculation system. The addition of exhaust gas recirculation with E30D70 in the common rail diesel engine exhibits oxides of nitrogen emission, but in contrast, it was noticed to have inferior performance characteristics and drastically decreased HC and CO emissions. The hydrocarbon emission decreased E10D90, E20D80, and E30D70 at 60% load condition by 21.42%, 37.38%, and 48.76%, respectively. The blends E10D90, E20D80, and E30D70 decreased carbon dioxide by 7.9%, 30.08%, and 31.98%, respectively. The maximum reduction of NOx emission was observed at about 51.06% at an EGR rate of 20% with E30D70.